Analysis of the export performance of state-owned enterprises from Latin American and Caribbean, reviewing corruption and informal economy. (16th April 2019) - Bertomeu, Gema Sancho-Miñana
State-owned enterprises from emerging economies have entered into an international expansion wave challenging the common assumption that these firms are limited to their domestic market. Literature however does not capture this new trend and address SOEs' activity from a limited viewpoint. Moreover, research on emerging economies and MNEs from these regions is rather general and clearly insufficient on the Latin American and Caribbean region. Following a quantitative strategy, we find that governments are strengthening the position of SOEs for different reasons other than just promoting exports. The institutional environment impacts the export performance of LAC SOEs, with informal economy facilitating the export performance of SOEs. Finally, data on corruption is slightly inadequate due to the sensitive of the topic, therefore a common framework for studying corruption is encouraged as it will both help advance research on the topic and help policy makers and practitioners to tackle corruption.